2019
DOI: 10.1177/0003319719875632
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of the Acute-to-Chronic Glycemic Ratio for In-Hospital Outcomes in Patients With ST-Segment Elevation Myocardial Infarction Undergoing Percutaneous Coronary Intervention

Abstract: This study investigated whether a novel index of stress hyperglycemia might have a better prognostic value compared to admission glycemia alone in patients with ST-segment elevation myocardial infarction (STEMI) undergoing percutaneous coronary intervention (PCI). The acute-to-chronic glycemic ratio was expressed as admission blood glucose (ABG) devided by the estimated average glucose (eAG), and eAG was derived from the glycated hemoglobin (HbA1c). A total of 1300 consecutive patients with STEMI treated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 42 publications
9
47
0
Order By: Relevance
“…Instead of ABG, both glycaemic gap and SHR were associated with major adverse cardiac events (MACEs) and could provide moderate predictive value for the occurrence of MACEs in AMI patients with DM [15,22,34]. Liao et al further demonstrated glycaemic gap rather than ABG was linked to all-cause mortality in acute heart failure (AHF) patients with DM [35].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Instead of ABG, both glycaemic gap and SHR were associated with major adverse cardiac events (MACEs) and could provide moderate predictive value for the occurrence of MACEs in AMI patients with DM [15,22,34]. Liao et al further demonstrated glycaemic gap rather than ABG was linked to all-cause mortality in acute heart failure (AHF) patients with DM [35].…”
Section: Discussionmentioning
confidence: 99%
“…High-performance liquid chromatography analysers were used to examine glycated haemoglobin (HbA 1 c) levels. Then, we obtained the estimated average glucose (eAG) level over the previous 3 months through the following equation: eAG = 28.7 * HbA1c − 46.7 [14,15,18], and glycaemic gap was calculated as ABG minus eAG. SHR, another index of relative hyperglycaemia, was defined as ABG/ eAG.…”
Section: Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…This index is calculated as ABG divided by the estimated average glucose (eAG). In recent studies, it has been found that the use of ABG/eAG ratio has an adequate performance compared to the use of absolute hyperglycemia for predicting poor cardiovascular outcomes, such as cardiogenic shock and acute pulmonary edema, both in non-diabetic and diabetic patients with STEMI [10,11].…”
Section: Introductionmentioning
confidence: 99%